The novel tetrahydropyrimidine derivative as inhibitor of SARS CoV-2: synthesis, modeling and molecular docking analysis - Genc, Zuhal Karagoz; Genc, Murat; Cosut, Bunyemin; Turgut, Mehmet (Taylor & Francis Inc, 2022)
N-(1,3-Benzothiazol-2-yl)-N-(1,4,5,6-tetrahydro-1H-pyrimidine-2-yl) amine was synthesized and characterized by elemental analysis, FT-IR, NMR and X-ray single crystal diffraction. The compound structure belongs to the triclinic system with the P-1 space group with unit cell parameters a = 11.9290(4), b = 13.2547(4) and c = 15.3904(5) A. Hirhsfeld surface analysis is performed to revealintermolecular interactions with these interactions. The molecular structure, vibrational spectroscopic data and HOMOs and LUMOs analyses were calculated by using the DFT/B3LYP method with the 6-311thornG(d,p)) basis set. Some of pharmacokinetic parameters and drug-likeness properties of the compound were also performed. Besides these, the present work is a searching to test N-(1,3-benzothiazol-2-yl)-N-(1,4,5,6-tetrahydro-1H-pyrimidine-2-yl) amine as an inhibitor for the SARS-CoV-2. For this aim, the molecular docking analysis of the synthesized compound was applied along with Favipiravir. Besides the docking results, ADMET properties of the compound were also calculated.
Keywords: Tetrahydropyrimidine; DFT/ B3LYP; SARS-CoV-2; ADMET; Drug-likeness